Galaxy Zoo: morphological classification of galaxy images from the Illustris simulation - Dickinson, Hugh; Fortson, Lucy; Lintott, Chris; Scarlata, Claudia; Willett, Kyle; Bamford, Steven; Beck, Melanie; Cardamone, Carolin; Galloway, Melanie; Simmons, Brooke; Keel, William; Kruk, Sandor; et al. (American Astronomical Society, 2018)
Modern large-scale cosmological simulations model the universe with increasing sophistication and at higher spatial and temporal resolutions. These ongoing enhancements permit increasingly detailed comparisons between the simulation outputs and real observational data. Recent projects such as Illustris are capable of producing simulated images that are designed to be comparable to those obtained from local surveys. This paper tests the degree to which Illustris achieves this goal across a diverse population of galaxies using visual morphologies derived from Galaxy Zoo citizen scientists. Morphological classifications provided by these volunteers for simulated galaxies are compared with similar data for a compatible sample of images drawn from the Sloan Digital Sky Survey (SDSS) Legacy Survey. This paper investigates how simple morphological characterization by human volunteers asked to distinguish smooth from featured systems differs between simulated and real galaxy images. Significant differences are identified, which are most likely due to the limited resolution of the simulation, but which could be revealing real differences in the dynamical evolution of populations of galaxies in the real and model universes. Specifically, for stellar masses, a substantially larger proportion of Illustris galaxies that exhibit disk-like morphology or visible substructure, relative to their SDSS counterparts. Toward higher masses, the visual morphologies for simulated and observed galaxies converge and exhibit similar distributions. The stellar mass threshold indicated by this divergent behavior confirms recent works using parametric measures of morphology from Illustris simulated images. When , the Illustris data set contains substantially fewer galaxies that classifiers regard as unambiguously featured. In combination, these results suggest that comparison between the detailed properties of observed and simulated galaxies, even when limited to reasonably massive systems, may be misleading.